Uncovering changes in microbiome profiles across commercial and backyard poultry farming systems - Muhammed Shafeekh Muyyarikkandy; Jessica Parzygnat; Siddhartha Thakur (Microbiology Spectrum, 2023)
ABSTRACT The microbiome profiles of poultry production systems significantly impact bird health, welfare, and the environment. This study investigated the influence of broiler-rearing systems on the microbiome composition of commercial and backyard chicken farms and their environment over time. Understanding these effects is vital for optimizing animal growth, enhancing welfare, and addressing human and environmental health implications. We collected and analyzed various samples from commercial and backyard farms, revealing significant differences in microbial diversity measurements between the two systems. Backyard farms exhibited higher alpha diversity measurements in soil and water samples, while commercial farms showed higher values for litter and feeder samples. The differences in microbial diversity were also reflected in the relative abundance of various microbial taxa. In backyard farms, Proteobacteria levels increased over time, while Firmicutes levels decreased. Campilobacterota, including the major poultry foodborne pathogen Campylobacter, increased over time in commercial farm environments. Furthermore, Bacteroides, associated with improved growth performance in chickens, were more abundant in backyard farms. Conversely, pathogenic Acinetobacter was significantly higher in backyard chicken fecal and feeder swab samples. The presence of Brevibacterium and Brachybacterium, associated with low-performing broiler flocks, was significantly higher in commercial farm samples. The observed differences in microbial composition and diversity suggest that farm management practices and environmental conditions significantly affect poultry health and welfare and have potential implications for human and environmental health. Understanding these relationships can inform targeted interventions to optimize poultry production, improve animal welfare, and mitigate foodborne pathogens and antimicrobial resistance risks. IMPORTANCE The microbiome of poultry production systems has garnered significant attention due to its implications on bird health, welfare, and overall performance. The present study investigates the impact of different broiler-rearing systems, namely, commercial (conventional) and backyard (non-conventional), on the microbiome profiles of chickens and their environment over time. Understanding the influence of these systems on microbiome composition is a critical aspect of the One-Health concept, which emphasizes the interconnectedness of animal, human, and environmental health. Our findings demonstrate that the type of broiler production system significantly affects both the birds and their environment, with distinct microbial communities associated with each system. This study reveals the presence of specific microbial taxa that differ in abundance between commercial and backyard poultry farms, providing valuable insights into the management practices that may alter the microbiome in these settings. Furthermore, the dynamic changes in microbial composition over time observed in our study highlight the complex interplay between the poultry gut microbiome, environmental factors, and production systems. By identifying the key microbial players and their fluctuations in commercial and backyard broiler production systems, this research offers a foundation for developing targeted strategies to optimize bird health and welfare while minimizing the potential risks to human and environmental health. The results contribute to a growing body of knowledge in the field of poultry microbiome research and have the potential to guide future improvements in poultry production practices that promote a sustainable and healthy balance between the birds, their environment, and the microbial communities they host.